Likelihood of Laryngeal Involvement in Autoimmune Thyroid Disorder Patients: A Meta-Analysis - Yue, Chuan; Gu, Li; Guo, Wei (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundThe involvement of the larynx in many situations can have a substantial impact on a person's voice, breathing, and general health. Individuals with autoimmune thyroid disorders can experience a variety of conditions affecting the larynx. Autoimmune thyroid disorders, such as Hashimoto's thyroiditis (HT) and Graves' disease (GD), are prevalent conditions affecting the thyroid gland. Beyond their established impact on thyroid function, these disorders have been associated with laryngeal involvement. The current study aims to explore the likelihood of laryngeal involvement in patients with Autoimmune Thyroid Disorders (AITD).MethodsThis study involved a retrospective analysis of medical records from patients diagnosed with autoimmune thyroid disorders. Inclusion criteria were a confirmed diagnosis through laboratory investigations and clinical assessment. Patients with pre-existing laryngeal pathologies or other conditions affecting the larynx were not considered. We collected data from 4 research articles and 3 clinical trials from Embase, PubMed, and NCBI-Trials portals, focusing on reported laryngeal symptoms. The severity of laryngeal involvement was assessed and categorized based on its extent and impact on vocal function.ResultsPreliminary analysis of the collected data indicated a significant proportion of patients with autoimmune thyroid disorders reporting laryngeal symptoms. Among these patients, various manifestations of laryngeal involvement were observed, including vocal changes, hoarseness, and throat discomfort.ConclusionThe findings show that laryngeal symptoms may be an underappreciated feature of these diseases, potentially impacting vocal function and quality of life in affected people. Further research is also needed for more precise projections in this direction.
Keywords: Laryngeal thyroid disorders